2005
DOI: 10.1177/154405910508401213
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic Stability of Self-etch Adhesives Bonded to Dentin

Abstract: Functional monomers chemically interact with hydroxyapatite that remains within submicron hybrid layers produced by mild self-etch adhesives. The functional monomer 10-MDP interacts most intensively with hydroxyapatite, and its calcium salt appeared most hydrolytically stable, as compared with 4-MET and phenyl-P. We investigated the hypothesis that additional chemical interaction of self-etch adhesives improves bond stability. The micro-tensile bond strength (muTBS) of the 10-MDP-based adhesive did not decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
174
0
20

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(205 citation statements)
references
References 17 publications
3
174
0
20
Order By: Relevance
“…5,59 Such chemical bond is mostly observed in mild and ultra-mild SE adhesives (pH < 2) that partially demineralizes dentin producing sub-micrometer hybrid layers 14 in which substantial HAp-crystals remain around partially exposed collagen fibers. 3,18,60,61 Besides protecting collagen fibers against degradation, such remaining mineral content also serves as receptor for additional chemical bonding with the respective functional monomer, 14,18 by which their two-fold bonding mechanism (i.e. micro-mechanical and chemical adhesion) closely resembles that of glass-ionomers.…”
Section: Chemical Bondingmentioning
confidence: 99%
“…5,59 Such chemical bond is mostly observed in mild and ultra-mild SE adhesives (pH < 2) that partially demineralizes dentin producing sub-micrometer hybrid layers 14 in which substantial HAp-crystals remain around partially exposed collagen fibers. 3,18,60,61 Besides protecting collagen fibers against degradation, such remaining mineral content also serves as receptor for additional chemical bonding with the respective functional monomer, 14,18 by which their two-fold bonding mechanism (i.e. micro-mechanical and chemical adhesion) closely resembles that of glass-ionomers.…”
Section: Chemical Bondingmentioning
confidence: 99%
“…Additionally, the organic debris might also be a reason for nanoleakage in the same manner that resin-impregnated smear layer formed in conventional self-etching procedure would cause nanoleakage. [26][27][28][29][30][31] Because it is known that such debris can be controlled by modifying atmospheric conditions at the irradiation field, 23 the quality of bonding strength following ArF excimer laser treatment might be further improved under decompression.…”
mentioning
confidence: 99%
“…This was a rather unusual result for a bonding system which already exhibited good initial bond strength. In previous studies, at best only a slight increase in bond strength was reported after long-term storage [19][20][21][22] . It has been suggested that loss of minerals from enamel and dentin during in vitro water storage would lead to deterioration of mechanical properties of teeth 31) .…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility of resin components to hydrolysis has been identified as a cause for decrease of bond strength. It has been suggested that the outstanding hydrolytic stability of MDP and its additional chemical interaction with enamel and dentin contributed to the long-term durability of dentin and enamel bonding with SE 17,21) and TS 18,22) . MDP has a special molecular structure that enables chemical interaction with residual hydroxyapatite after etching, and the calcium salts formed thereby also exhibit hydrolytic stabiltiy 21) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation